Synbiotic sheep milk ice cream reduces chemically induced mouse colon carcinogenesis - Balthazar, Celso F.; de Moura, Nelci A. [UNESP]; Romualdo, Guilherme R. [UNESP]; Rocha, Ramon S.; Pimentel, Tatiana C.; Esmerino, Erick A.; Freitas, Mônica Q.; Santillo, Antonella; Silva, Marcia Cristina; Barbisan, Luis F.; Cruz, Adriano G.; Albenzio, Marzia (American Dairy Science Association, 2021)
Sheep dairy products containing prebiotic and probiotic ingredients may have health-promoting properties. Thus, this study evaluated the effects of sheep milk ice cream [conventional full-fat (CONV), full-fat enriched with probiotic (PROB, 100 mg % wt/wt of Lacticaseibacillus casei 01), or nonfat synbiotic (SYNB, Lacticaseibacillus casei 01 and inulin, 10% wt/wt)] on carcinogen-induced colonic crypt cytotoxicity and premalignant lesion development. Male Swiss mice received 2 doses of colon carcinogen azoxymethane (AOM, 15 mg/kg of body weight) at wk 3 and 4. Two weeks before and during AOM administrations (4 wk) mice were treated with CONV, PROB, or SYNB by gavage (10 mL/kg). Mice were euthanized at wk 4 or 25 (n = 5 or 10 mice/group, respectively). At wk 4, a significant reduction in micronucleated colonocytes was observed in PROB and SYNB groups, and a significant decrease in both p53 expression and apoptosis indexes in colonic crypts was observed in SYNB group. At wk 25, both PROB and SYNB interventions reduced the mean number of colonic premalignant lesions. However, only SYNB group showed lower incidence and number of high-grade premalignant lesions in the colonic mucosa. These findings indicate that PROB or SYNB sheep milk ice cream, especially SYNB intervention, can reduce chemically induced mouse colon carcinogenesis.
Keywords: azoxymethane; colon carcinogenesis; sheep dairy food; synbiotic